The Concept of Human Soul according to Karl Rahner. Ideas - Controversies – Alternatives. - Machinek, Marian (Filozofia Chrześcijańska, 2010)
At the heart of Karl Rahner's theological thought lies the relationship between spirit and matter, and his reflection on the soul should be read in this broad context. Since both spirit and matter have their origins in the same Creator, they are both mutually subjected to each other in such a way that matter is directed towards spirit. The qualitative elevation of matter is possible thanks to its active self-transcendence. Though this self-transcendence of matter results from its own dynamic activity, by no means does it happen by the power of its own nature. The driving force behind it, working 'from within it', comes from the creative power of God, who alone is the primal cause of every being. By constructing this concept, Rahner hopes to avert a danger of falling into a trap of anthropological dualism, in which the substantial unity of man gives way to a blend of two distinct elements. He also avoids the anthropomorphism of the Creator's acts, which would mean a reduction of God to a mythological demiurg, who merely perfects those beings that had already been created. Rahner's concept was widely discussed in academic circles, and criticised by some scholars. Despite his unambiguous declarations of adherence to classical metaphysics and the Magisterium of the Catholic Church, some ascribe him the idea of spiritualization of the matter; an idea which would be tantamount to a kind of ontological monism. Moreover, Rahner appears to combine the activities of the primal cause with the secondary ones. Some alternative concepts, while taking into account Rahner's basic proposals, seek to avoid the above mentioned problems by reducing the time gap between the fundamental teachings about the Creation: creatio originalis and creatio continua. Thus the acceptance of the theory of God's direct activity does not necessarily lead to his unacceptable anthropomorphism.